Sinergi Administrasi Publik dan Nilai Islam Dalam Mewujudkan Tata Kelola Remaja Masjid Kota Blitar yang Profesional dan Islami - Jalu Sora Wicitra; Putri Cinta Mei (Jurnal Pengabdian Masyarakat Waradin, 2025)
The Mosque Youth Organization (REMAS) plays an important and strategic role as an agent of social and religious change among the younger generation. This study aims to improve the governance of the Mosque Youth Organization in Blitar City to be more professional and Islamic through the synergy of public administration and Islamic values. The main problems faced include a lack of coordination with the mosque administrators, a lack of effective leadership, and low community participation, which are influenced by internal factors such as the busyness of members and external factors such as limited funds and facilities. The method used is a participatory approach through needs analysis with 20 REMAS and mosque administrators, followed by training on professional Islamic governance, management skills, and evaluation assistance for its implementation. The training was held at the Al Mugi Barokah Mosque in Blitar City in September 2025, in collaboration with the Indonesian Mosque Youth Communication Agency (BKPRMI) as a stakeholder. The results of the community service showed significant improvements, namely the formation of a clear organizational structure, community-based work programs such as skills training and innovative social activities, and effective coordination with mosque administrators through regular forums to increase community participation. This approach integrates good governance principles such as transparency, accountability, and documentation using Trello or Google Sheets with Islamic values such as deliberation, trustworthiness, benevolence, and the example set by the Prophet Muhammad SAW. These activities contribute to sustainable social transformation among mosque youth, strengthening their role as agents of socio-religious change, although challenges such as limited resources, internal conflicts, and slow technological adaptation still need to be addressed through regular monitoring and further technological integration.